Evaluating a training program in terms of the lactic differential threshold and some respiratory indicators for hurdle youth runners in 3000 meters race - Bahri Shamkhi Hussein, Ghassan; Fadhil Alwan, Muhammad; Ataallah Essa Alobayde, Waleed (International Journal of Psychosocial Rehabilitation, 2020)
The world witnessed at the present time progress scientifically significant in the application of modern scientific bases in the sports field, which has become a key pillar count on raising the level of performance and the get advanced results in many games and sports events, including the activities of athletics, which date significant progress in the i leaflet performance Ha and the level is higher functionally and physically. The importance of research lies in the interest in athletics activities, including running 3000 m hindrances. Therefore, scientific methods must be adopted in training and the need to use appropriate means to explore the functional capabilities inherent in the athlete’s body represented by the functional capabilities of the circulatory and respiratory systems during sports training, as well as providing the requirements for muscular work. Crystallized research problem in identifying the capabilities of a group of runners to the effectiveness of (3000 m steeplechase) and functional physical and study them on according to the type of training or training program , and through that we can evaluate this program or training curriculum in terms of the threshold distinguishing index values indicators functional Other Under study for players, including maximum oxygen consumption, respiratory frequency, heart rate, pulmonary ventilation, as well as level of physical abilities through physical activity tests. The aim of the study to identify the threshold distinguishing index values and some device indicators of respiratory research sample under study, the imposition of the researcher Wen presence differences y and the data statistically significant differences between the test yen pre and post the results of indicators functional and for post - test for the research sample under study. The researchers used the experimental approach on 6 of those who ran the effectiveness of 3000 m. Contraindications, and after analyzing and treating the values of the studied functional indicators of the research sample, the researchers reached several conclusions, including the differential threshold indicator, the effective role of improving the functional status of runners, and the recommendations were to conduct monthly periodic tests of the players ’functional indicators to know the effectiveness of the training program used for runners.